Poster: A step towards smart traffic sign board by smart devices - Gautam S.; Gupta H.P.; Dutta T. (My University, 2025)
A Traffic Sign Board (TSB) provides advance information about road conditions ahead, orders, warning, or guidance to the road users. The traditional TSBs use sign boards as a signal for vehicles and expect the drivers to be aware the sign board. In some scenarios, such as rains, traffic jam, light intensity, and vehicle speed, reduce the visibility of the TSBs. In this work, we proposed a smart traffic sign board system using Bluetooth Low Energy (BLE). The system op- portunistically advertises the TSB information to road users (e.g., drivers, passengers, and riders) using BLE. © 2016 Copyright held by the owner/author(s).